Streptococcus halichoeri: Comparative Genomics of an Emerging Pathogen - Kirsi Aaltonen; Ravi Kant; Marjut Eklund; Mirja Raunio-Saarnisto; Lars Paulin; Olli Vapalahti; Thomas Grönthal; Merja Rantala; Tarja Sironen (International Journal of Genomics)
Streptococcus halichoeri is an emerging pathogen with a variety of host species and zoonotic potential. It has been isolated from grey seals and other marine mammals as well as from human infections. Beginning in 2010, two concurrent epidemics were identified in Finland, in fur animals and domestic dogs, respectively. The fur animals suffered from a new disease fur animal epidemic necrotic pyoderma (FENP) and the dogs presented with ear infections with poor treatment response. S. halichoeri was isolated in both studies, albeit among other pathogens, indicating a possible role in the disease etiologies. The aim was to find a possible common origin of the fur animal and dog isolates and study the virulence factors to assess pathogenic potential. Isolates from seal, human, dogs, and fur animals were obtained for comparison. The whole genomes were sequenced from 20 different strains using the Illumina MiSeq platform and annotated using an automatic annotation pipeline RAST. The core and pangenomes were formed by comparing the genomes against each other in an all-against-all comparison. A phylogenetic tree was constructed using the genes of the core genome. Virulence factors were assessed using the Virulence Factor Database (VFDB) concentrating on the previously confirmed streptococcal factors. A core genome was formed which encompassed approximately half of the genes in Streptococcus halichoeri. The resulting core was nearly saturated and would not change significantly by adding more genomes. The remaining genes formed the pangenome which was highly variable and would still evolve after additional genomes. The results highlight the great adaptability of this bacterium possibly explaining the ease at which it switches hosts and environments. Virulence factors were also analyzed and were found primarily in the core genome. They represented many classes and functions, but the largest single category was adhesins which again supports the marine origin of this species.